2018
DOI: 10.14341/dm9533
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hyperinsulinemic – hypoglycemic clamp on induced platelet aggregation, activity of physiological anticoagulants and von Willebrand factor in patients with type I diabetes

Abstract: ОБОСНОВАНИЕ. Гипогликемия у больных сахарным диабетом 1 типа (СД1) вследствие коррекции гипергликемии может являться фактором риска развития сердечно-сосудистых и цереброваскулярных осложнений. Одной из при-чин этих осложнений может быть активация тромбоцитарного и плазменного звена гемостаза при недостаточности физиологических антикоагулянтов. ЦЕЛЬ.Оценка влияния контролируемого перехода от гипергликемии к эугликемии и затем к гипогликемии на инду-цированную агрегацию тромбоцитов, активность физиологических а… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The studies that showed increased platelet hyperactivity concurrent with hyperinsulinemia induced hypoglycemia [94], with attendant increase in counter-regulatory hormones such as adrenaline [111,112] and increase in vWF-platelet adhesiveness [24], results which were similar to findings in T2DM [113].…”
Section: Insulin Treatmentmentioning
confidence: 70%
See 1 more Smart Citation
“…The studies that showed increased platelet hyperactivity concurrent with hyperinsulinemia induced hypoglycemia [94], with attendant increase in counter-regulatory hormones such as adrenaline [111,112] and increase in vWF-platelet adhesiveness [24], results which were similar to findings in T2DM [113].…”
Section: Insulin Treatmentmentioning
confidence: 70%
“…Administration of insulin pre-meal was accompanied by increase of postprandial platelet activation markers [74,76,93]. However, platelet-activating effects of insulin in T1DM are evident only when there is concurrent hypoglycemia [94]. At low extracellular glucose, insulin potentiates action of thrombin to increase glucose entry via Glut-3 with concomitant increase in surface expression of P-selectin and aggregation.…”
Section: Blood Glucose and Platelet Functions In T1dmmentioning
confidence: 99%